An Update on the Role of Dietary Phytochemicals in Human Skin Cancer: New Insights into Molecular Mechanisms - Islam, Salman Ul (Antioxidants (Basel), 2020)
Human skin is continuously subjected to environmental stresses, as well as extrinsic and intrinsic noxious agents. Although skin adopts various molecular mechanisms to maintain homeostasis, excessive and repeated stresses can overwhelm these systems, leading to serious cutaneous damage, including both melanoma and non-melanoma skin cancers. Phytochemicals present in the diet possess the desirable effects of protecting the skin from damaging free radicals as well as other benefits. Dietary phytochemicals appear to be effective in preventing skin cancer and are inexpensive, widely available, and well tolerated. Multiple in vitro and in vivo studies have demonstrated the significant anti-inflammatory, antioxidant, and anti-angiogenic characteristics of dietary phytochemicals against skin malignancy. Moreover, dietary phytochemicals affect multiple important cellular processes including cell cycle, angiogenesis, and metastasis to control skin cancer progression. Herein, we discuss the advantages of key dietary phytochemicals in whole fruits and vegetables, their bioavailability, and underlying molecular mechanisms for preventing skin cancer. Current challenges and future prospects for research are also reviewed. To date, most of the chemoprevention investigations have been conducted preclinically, and additional clinical trials are required to conform and validate the preclinical results in humans.